Dust‐infused baroclinic cyclone storm clouds: The evidence, meteorology, and some implications. Issue 24 (30th December 2016) - Fromm, Michael; Kablick, George; Caffrey, Peter
Abstract: Desert mineral dust is a critical yet still poorly understood component of atmospheric composition, weather, and climate. Long‐range transport of dust is well known, yet uncertainty persists regarding the pathway from the desert floor to the free troposphere. Here we will show that a recurrent pathway for dust into the uppermost troposphere involves passage through an extratropical baroclinic cyclonic storm. The evidence derives from a synergistic use of satellite‐based, multispectral nadir‐image data and lidar. The dust‐infused baroclinic storm (DIBS) exhibits peculiar cirrus cloud top reflected and emitted radiance from the UV through thermal IR, involving positive UV absorbing aerosol index, muted visible reflectivity, visible cumuliform texture, and systematically intense visible lidar backscatter on a synoptic scale. Proof that the DIBS is microphysically impacted by storm‐scale dust infusion is the occurrence of anomalously large daytime 3.9–11μm brightness temperature difference indicative of small ice crystals. We present multispectral snapshots of two DIBS, over two desert source regions, in comparison with a pristine baroclinic storm cloud. Each storm snapshot is presented in the context of the baroclinic cyclone's lifetime and dust source region (the Gobi desert and the Sahara). These and other cases discussed show that the DIBS is a recurring conduit for long‐range transport and a natural experiment in dust‐related aerosol indirect effects. Key Points: Desert dust observed in tropopause level ice clouds DIBS storms are connected with recurrent intercontinental dust transport DIBS ice clouds have a unique cellular structure